Analysis of Heat Transfer of Cu-Water Nanofluid Flow Past a Moving Wedge - Shanmugapriya, M. (Journal of Informatics and Mathematical Sciences, 2018)
In this paper, heat transfer of a steady, two-dimensional, incompressible Cu-water nanofluid flow over a moving wedge in the presence of thermal radiation effect are investigated. Gyarmati’s variational principle developed on the thermodynamic theory of irreversible processes is employed to solve the problem numerically. The governing boundary layer equations are approximated as simple polynomial functions, and the functional of the variational principle is constructed. The Euler-Langrange equations are reduced to simple polynomial equations in terms of boundary layer thicknesses. The velocity and temperature profiles as well as skin friction and heat transfer are analyzed for various parameters. The obtained numerical solutions are compared with the previously published results and are found to be in good agreement.